Centralized daily drug management in clinical trial institutions and specific implementation plans - Yu Tang; Yu Tang; Xiaolong Fang (Frontiers in Drug Safety and Regulation)
BackgroundExperimental drug management is an important part of clinical trial management and directly relates to the reliability of clinical trial data and the safety of participants. This study explores the implementation of centralized pharmacy management in clinical drug trials, addressing the limitations of decentralized approaches.MethodsIt involves the establishment of a centralized drug warehouse with unified processes and digital systems, primarily relying on the Cold Chain Cloud Platform, Service Cloud Platform, and Enterprise WeChat Platform, to enhance precision and efficiency.ResultsIt indicated a significant reduction in error rates and improved adherence to clinical trial protocols. The centralized model also minimized protocol deviations and strengthened participant safety.ConclusionIt highlights the benefits of centralized management in enhancing drug administration efficiency and maintaining high standards of trial conduct, suggesting future integration with Artificial Intelligence (AI) and Electronic Health Records (EHR) for more precise pharmaceutical services.